C1-3: Longitudinal Predictors of Initial and Repeat Colorectal Cancer Screening - Murphy, Caitlin (Clin Med Res, 2014)
BACKGROUND/AIMS: Few studies have used longitudinal data to examine predictors of colorectal cancer screening (CRCS). Further, there has been little research on repeat, on-schedule CRCS. METHODS: We conducted a secondary analysis of data from the Systems of Support to Increase Colorectal Cancer Screening Trial (SOS), a randomized trial to increase CRCS in adults not current with screening recommendations. The sample consisted of 1,247 participants that completed a supplemental survey at baseline. Potential predictors included sociodemographics, medical/health history, intervention group assignment, and previously validated scales of CRCS pros, cons, self-efficacy, social influence, and cancer worry. Univariable and multivariable analyses were used to identify predictors of: 1) CRCS completion during the first year of the study, and 2) repeat, on-schedule CRCS during the second year of the study among those that completed an FOBT in Year 1. We also tested for moderation effects of the intervention on baseline predictors of screening completion. RESULTS: In multivariable analysis, prior CRCS at baseline (OR 2.67, 95% CI 2.01–3.55) and intervention group assignment (Automated: OR 2.06 95% CI 1.44–2.96; Assisted: OR 3.97, 95% CI 2.65–5.92; Navigated: OR 5.65, 95% CI 3.76–8.49) were statistically significant predictors of CRCS completion at Year 1. Family history of colorectal cancer, higher self-efficacy, and higher health rating trended towards significance. For repeat CRCS at Year 2, prior CRCS at baseline (OR 1.97, 95% CI 1.26–3.07), intervention group (Automated: OR 9.97, 95% CI 4.97–19.98; Assisted: OR 12.34, 95% CI 6.07–25.09; Navigated: OR 14.44, 95% CI 1.06–29.52) and self-efficacy (OR 1.35, 95% CI 1.03–1.77) were statistically significant predictors. The intervention moderated the effect of prior CRCS and smoking status on CRCS completion at Year 1: 79.5% with prior CRCS were screened vs. 55.2% with no prior CRCS and 70.2% of non-smokers were screened vs. 53.9% of current smokers. CONCLUSIONS: Prior screening experience was a significant determinant of CRCS in both years 1 and 2, and the intervention amplified the effect of prior screening in Year 1. The intervention also was an important determinant of screening in both years suggesting that removing major access barriers increased screening completion.